Binding characterization of N‐(2‐chloro‐5‐thiomethylphenyl)‐N′‐(3‐[3H]3methoxy phenyl)‐N′‐methylguanidine ([3H]GMOM), a non‐competitive N‐methyl‐D‐aspartate (NMDA) receptor antagonist. Issue 1 (19th February 2019) - Metaxas, Athanasios; van Berckel, Bart N. M.; Klein, Pieter J.; Verbeek, Joost; Nash, Emily C.; Kooijman, Esther J. M.; Renjaän, Véronique A.; Golla, Sandeep S. V.; Boellaard, Ronald; Christiaans, Johannes A. M.; Windhorst, Albert D.; Leysen, Josée E.
Abstract: Labeled with carbon‐11, N ‐(2‐chloro‐5‐thiomethylphenyl)‐ N ′‐(3‐methoxyphenyl)‐ N ′‐methylguanidine ([ 11 C]GMOM) is currently the only positron emission tomography (PET) tracer that has shown selectivity for the ion‐channel site of N ‐methyl‐D‐aspartate (NMDA) receptors in human imaging studies. The present study reports on the selectivity profile and in vitro binding properties of GMOM. The compound was screened on a panel of 80 targets, and labeled with tritium ([ 3 H]GMOM). The binding properties of [ 3 H]GMOM were compared to those of the reference ion‐channel ligand [ 3 H](+)‐dizocilpine maleate ([ 3 H]MK‐801), in a set of concentration‐response, homologous and heterologous inhibition, and association kinetics assays, performed with repeatedly washed rat forebrain preparations. GMOM was at least 70‐fold more selective for NMDA receptors compared to all other targets examined. In homologous inhibition and concentration‐response assays, the binding of [ 3 H]GMOM was regulated by NMDA receptor agonists, albeit in a less prominent manner compared to [ 3 H]MK‐801. Scatchard transformation of homologous inhibition data produced concave upward curves for [ 3 H]GMOM and [ 3 H]MK‐801. The radioligands showed bi‐exponential association kinetics in the presence of 100 μmol L −1 l ‐glutamate/30 μmol L −1 glycine. [ 3 H]GMOM (3 nmol L −1 and 10 nmol L −1 ) was inhibited with dual affinity by (+)‐MK‐801, ( R, S )‐ketamine and memantine, in both presence and absence of agonists. [ 3 H]MK‐801 (2 nmol L −1 ) was inhibited in a monophasic manner by GMOM under baseline and combined agonist conditions, with an IC50 value of ~19 nmol L −1 . The non‐linear Scatchard plots, biphasic inhibition by open channel blockers, and bi‐exponential kinetics of [ 3 H]GMOM indicate a complex mechanism of interaction with the NMDA receptor ionophore. The implications for quantifying the PET signal of [ 11 C]GMOM are discussed.